Tetradentate Schiff Base Chelates of Copper(II) and Nickel(II):Halogenation and Phenylisocyanation - Lilly, K.O.; Balasubramanian, V.; Merlin, M.; Christopher Kanagam, Charles (Asian Journal of Chemistry, 2012)
Halogenation (chlorination, bromination and iodination) and phenyl isocyanation reactions are conducted on newly synthesized bis(polyamines acetylacetoneimine) of nickel(II) and copper(II).